2019
DOI: 10.1101/680058
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mycobacterium tuberculosisinfection boosts B cell responses to unrelated pathogens

Abstract: Significance 42Mycobacterium tuberculosis (M.tb) has potent immunostimulatory properties and has been used in 43 adjuvant preparations to improve vaccine responses in animals. This study shows that natural M.tb 44 infection in humans is associated with increased antibody and B cell recall responses to heterologous 45 pathogens. This data suggests a potential role for M.tb antigens in immunotherapies designed to 46 maintain antibody immunity to diverse infections. 47

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 33 publications
(30 reference statements)
3
5
1
Order By: Relevance
“…Our study demonstrates the significant enhancement of antibody titres against heterologous pathogens following low-dose M.tb challenge in NHPs. This is consistent with the findings of Kimuda et al, who observed higher heterologous antibody responses in patients with pulmonary TB disease compared with uninfected controls in Uganda, and provides validation of this effect in a more controlled system that enables the direct comparison of matched preand post-infection samples (40). Once the human data were adjusted for potential confounders, active TB was associated with higher levels of anti-RSV and anti-measles antibodies compared to the uninfected individuals (40).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study demonstrates the significant enhancement of antibody titres against heterologous pathogens following low-dose M.tb challenge in NHPs. This is consistent with the findings of Kimuda et al, who observed higher heterologous antibody responses in patients with pulmonary TB disease compared with uninfected controls in Uganda, and provides validation of this effect in a more controlled system that enables the direct comparison of matched preand post-infection samples (40). Once the human data were adjusted for potential confounders, active TB was associated with higher levels of anti-RSV and anti-measles antibodies compared to the uninfected individuals (40).…”
Section: Discussionsupporting
confidence: 88%
“…The current study aimed to determine whether infection with M.tb, or vaccination with BCG or MTBVAC, influences antibody responses to a range of unrelated pathogens. Kimuda et al have previously shown that active pulmonary TB patients in Uganda had higher antibody responses to respiratory syncytial virus (RSV) and measles virus (MV) compared with uninfected controls, while BCG vaccination in uninfected UK adults did not alter levels of antibodies against heterologous pathogens (40). There were some limitations to this study including inability to measure matched pre-and post-M.tb infection responses in the same individuals, and the unknown time after infection that samples were collected.…”
Section: Introductionmentioning
confidence: 99%
“…The optical, (piezo)electrical, or (micro)mechanical transducers are among the promising methods for recognizing ligand-receptor interaction signals in label-free biosensors used for the diagnosis of various infectious diseases. These biosensing methods are enhanced by surface plasmon resonance (SPR) [78], surface Raman spectrometry (SERS) [36,38,39], quartz crystal microbalance [86], and microcantilever sensors [78,87,88].…”
Section: Label-free Biosensorsmentioning
confidence: 99%
“…The biosensors with optical transducers, considered as the main tools for signal perception, are one of the most powerful detection and analysis tools widely used in biomedical research and practical medicine [8,9,72,88,89]. These transducers are based on measuring changes in optical properties in the presence of the analyte, such as absorption, reflectivity, radiation, or interferometric pattern, which can be detected by a photodetector.…”
Section: Label-free Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation